PERSEPSI SISWA TERHADAP MODEL PEMBELAJARAN BERBASIS OTAK (MPBO) DALAM PEMBELAJARAN MEMBACA PEMAHAMAN - Kohar, Dadun (UNIB Press, 2023)
This study aims to determine students’ perception of the Brain-Based Learning Model (MPBO) in learning of comprehension reading. This study uses a descriptive method with a qualitative approach. The data collection technique used is a questionnaire in the form of a Likert scale. The data for each variable is processed by the following steps: grouping the data, tabulating the data, presenting the data in tabular form, calculating scores, presenting the data in the form of pictures, and drawing conclusions both for each variable and as a whole. This study concludes that students consider MPBO is good when used in learning of comprehension reading. This can be seen from the perception score given by students, which is 424. If it is presented, the score becomes 84.50%. This means that students' perceptions are slightly agree.